2019
DOI: 10.1002/acn3.50894
|View full text |Cite
|
Sign up to set email alerts
|

Altered long noncoding RNA profile after intracerebral hemorrhage

Abstract: ObjectiveWe investigated the expression pattern of long noncoding RNAs (lncRNA) and messenger RNAs (mRNA) from two different intracerebral hemorrhage (ICH) rat models, and performed gene ontology and gene/protein interaction analyses.MethodsWe harvested hemorrhagic brain 1, 3, and 7 days after ICH induction by stereotactic collagenase injection. We performed microarray analyses with Agilent array platform to compare the expression of lncRNA and mRNAs from hemorrhagic and normal brains. The RNA expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…This study first revealed the temporal expression pattern of lncRNAs with an acute hemorrhagic stroke model induced by stereotactic collagenase injection. Gene ontology/pathway analysis revealed that inflammation is a key biological process after a hemorrhagic stroke and functional study disclosed that lncRNA H19 was the most upregulated lncRNA after intracerebral hemorrhage and closely related to the type I interferon signaling pathway (Kim et al, 2019). Therefore, lncRNA H19 plays an important role both in ischemic stroke and intracerebral hemorrhage.…”
Section: Lncrnas In Intracerebral Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations
“…This study first revealed the temporal expression pattern of lncRNAs with an acute hemorrhagic stroke model induced by stereotactic collagenase injection. Gene ontology/pathway analysis revealed that inflammation is a key biological process after a hemorrhagic stroke and functional study disclosed that lncRNA H19 was the most upregulated lncRNA after intracerebral hemorrhage and closely related to the type I interferon signaling pathway (Kim et al, 2019). Therefore, lncRNA H19 plays an important role both in ischemic stroke and intracerebral hemorrhage.…”
Section: Lncrnas In Intracerebral Hemorrhagementioning
confidence: 99%
“…The role of lncRNAs in intracerebral hemorrhage is an attractive field that scientists have tried to elucidate with limited success. Kim et al (2019) performed microarray analyses and found that 83, 289, and 401 lncRNAs were significantly upregulated, whereas 52, 489, and 786 lncRNAs were significantly decreased of 1, 3, and 7 days after intracerebral hemorrhage, respectively. This study first revealed the temporal expression pattern of lncRNAs with an acute hemorrhagic stroke model induced by stereotactic collagenase injection.…”
Section: Lncrnas In Intracerebral Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are consisted of more than 200 nucleotides, although, less abundant compared to miRs they show more microenvironment-dependent function [ 70 ] and have regulatory roles in a variety of metabolic processes in the nucleus and cytoplasm [ 71 ]. In recent years, the function of different lncRNAs in expression regulation after stroke is studied more extensively, especially in inflammation [ 72 , 73 , 74 ]. Interestingly, lncRNA may regulate the expression of genes coding for miRs.…”
Section: Epigenetic Regulation Of Immune Response In Strokementioning
confidence: 99%
“…Peripheral blood cells play vital roles in the brain injury caused by ICH, and previous studies have reported that noncoding RNA (ncRNA) expression pro les are altered rapidly in the blood [9][10][11]. CircRNAs are a large class of ncRNAs produced by back-splicing [12].…”
Section: Introductionmentioning
confidence: 99%